Estudio clínico epidemiológico de pacientes con lupus eritematoso sistémico en un hospital de la Amazonía Peruana de 2019-2023 - Rodriguez Siguas, Nelly Gabriela (2026)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a variable course and multisystem involvement, primarily affecting women of reproductive age. It is characterized by wide clinical and serological heterogeneity, with potential involvement of the skin, joints, kidneys, hematologic, cardiovascular, and nervous systems, which complicates timely diagnosis and therapeutic management. Worldwide, it is estimated that around five million people suffer from SLE, with a higher burden on vulnerable populations. In Peru, the approximate prevalence is 50 cases per 100,000 inhabitants, with a higher concentration observed in rural areas and indigenous communities, as seen in the Loreto region. Despite advances in the survival of patients with SLE, mortality remains higher than in the general population, especially in those with high disease activity, kidney involvement, infections, and hematologic abnormalities. The absence of The absence of a single, specific biomarker requires integrating clinical findings with the results of serological and immunological tests, such as antinuclear antibodies (ANA), anti-double-stranded DNA, complement levels, and hematological alterations, following diagnostic criteria such as those proposed by ACR/EULAR. This study aims to analyze the relationship between serological marker positivity and clinical and epidemiological manifestations in patients with systemic lupus erythematosus treated at the Regional Hospital of Loreto. It seeks to describe the clinical profile, relevant laboratory findings, and treatments used, with the goal of contributing to a more accurate diagnosis and better therapeutic decision-making in the region. The research is justified by the clinical and epidemiological relevance of SLE in Loreto, where its management is challenged by the variability of manifestations and the comple The complexity of the disease. The study is feasible due to access to medical records, institutional support, and the availability of human and material resources. However, its main limitation is the possible incompleteness of the medical records and the use of diagnostic criteria prior to those established by EULAR/ACR 2019.